1998
DOI: 10.1002/(sici)1096-8628(19980605)77:5<431::aid-ajmg15>3.3.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Anomalies in Down syndrome individuals in a large population‐based registry

Abstract: In a population of close to 2.5 million infants born from 1983 to 1993 registered in the California Birth Defects Monitoring Program, we compared the prevalence of structural birth defects among 2,894 infants with Down syndrome (DS) with that of infants without DS. Among 61 defects uniformly ascertained in affected and unaffected infants, 45 were significantly more common in DS, with atrioventricular canal (risk ratio = 1,009), duodenal atresia (risk ratio = 265), and annular pancreas (risk ratio = 430) being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
105
3
7

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(131 citation statements)
references
References 22 publications
16
105
3
7
Order By: Relevance
“…The mapping of the triplicated genomic segment of chromosome 21 that harbors the functional elements contributing to congenital heart defect (CHD) 46,47 is of importance to understand the pathogenesis of these anomalies. CHD is present in only 2/12 (17%) compared to the overall risk of CHD of 40% reported in DS patients.…”
Section: Partial Trisomy 21 and Critical Regionsmentioning
confidence: 99%
“…The mapping of the triplicated genomic segment of chromosome 21 that harbors the functional elements contributing to congenital heart defect (CHD) 46,47 is of importance to understand the pathogenesis of these anomalies. CHD is present in only 2/12 (17%) compared to the overall risk of CHD of 40% reported in DS patients.…”
Section: Partial Trisomy 21 and Critical Regionsmentioning
confidence: 99%
“…Sites abstracted infant records and entered the information onto a structured clinical form, which was then reviewed by a Table 1 Population-based studies of congenital heart defects in down syndrome Freeman et al 2 and unpublished Kallen et al 3 Stoll et al 4 Torfs and Christianson 5 Current study single clinically trained individual at Emory. The presence or absence of CHDs, the particular heart defect(s) diagnosed, and the date and method(s) of diagnosis were recorded for each infant.…”
Section: Clinical Informationmentioning
confidence: 99%
“…In 1998 the Atlanta Down syndrome Project (ADSP), a forerunner of the NDSP, reported that 41% of newborns with DS were born with one or more major heart defects, including atrioventricular septal defect (AVSD), secundum atrial septal defect (ASDII), ventricular septal defect (VSD), and tetralogy of Fallot (TOF). 2 Findings from the ADSP and other recent population-based studies of DS and CHDs [2][3][4][5] are summarized in Table 1.…”
mentioning
confidence: 99%
“…It occurs in about 1 in 700 births, and is more common in males [1]. Most children are diagnosed on basis of phenotypic findings like, flat nasal bridge, poor muscle tone, a small head, upward slanting eyes, epicanthal folds, small ears, small mouth, dermographics (ulner loops, single palmer crease, and distal tri-radii), clinodactyly, large tongue, and a large space between toes (sandal gap).…”
Section: Introductionmentioning
confidence: 99%